(untitled) (Nuntius Antiquus, 2010)
The article aims to understand specific aspects of the relations between emperors and aristocrats, especially regarding the role of clemency in the making of these relationships. The authors analyse this issue in the context of the principates of Claudius and Nero in three works of Seneca (De consolatione ad Polybium, Apolococintosis, De clementia).